Analysis of Patient Complaint Handling Management Regarding Health Services in Maintaining Hospital Quality - Muftiana Finansi Ekawati; Rahmat Bakhtiar; Blego Sedionoto (GLOBAL HEALTH SCIENCE GROUP, 2025)
Complaints received by hospitals from patients and their families have the potential to provide (early) warnings that, if followed up, can prevent patient safety incidents. Complaints about services can be used to improve the standard of health facility services. Therefore, organizing complaint forms for hospitals minimizes complaints in the hope of reducing the risk of patient safety hazards and improving the quality of hospital services. This study aims to analyze and explore the management of complaint handling at Balikpapan Baru Hospital. Using a qualitative research method with a phenomenological approach with researchers as instruments. In-depth interviews with 5 informants through purpose sampling techniques. Data sources in the form of patient complaints for the period July-November 2023. Most patient complaints were related to the behavior (communication method) of health workers, patients who submitted complaints were directly directed to fill in and there were obstacles in the form of differences in perception of complaint categories by health workers. Complaint handling management at Balikpapan Baru Hospital is managed by team and involves various units. There were obstacles in the form of different perceptions in filling out the form and different responses regarding complaint handling related to communication between health workers.